2010
DOI: 10.1152/japplphysiol.00576.2010
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant ventilatory and circulatory functions of the diaphragm and abdominal muscles

Abstract: Expulsive maneuvers (EMs) caused by simultaneous contraction of diaphragm and abdominal muscles shift substantial quantities of blood from the splanchnic circulation to the extremities. This suggests that the diaphragm assisted by abdominal muscles might accomplish ventilation and circulation simultaneously by repeated EMs. We tested this hypothesis in normal subjects by measuring changes (Δ) in body volume (Vb) by whole body plethysmography simultaneously with changes in trunk volume (Vtr) by optoelectronic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 22 publications
5
53
0
5
Order By: Relevance
“…Furthermore, the most of others parameters of the cardiac function such as ejection fraction, aortic pressure, and pulmonary arterial pressure, preload and afterload and even tissue oxygenation have been shown to be modelocked to breathing [43,44]. Diaphragmatic contractions also increase cardiac output under conditions of preload dependency, which has actually been observed in healthy humans [45] and in patients with cardiac pacemakers, in whom diaphragmatic contractions were induced via the pacemaker [46]. Interestingly, D'Alonzo and Krachman have also shown that poor diaphragm biomechanics may lead to decreased cardiac output [47].…”
Section: Cardiac Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the most of others parameters of the cardiac function such as ejection fraction, aortic pressure, and pulmonary arterial pressure, preload and afterload and even tissue oxygenation have been shown to be modelocked to breathing [43,44]. Diaphragmatic contractions also increase cardiac output under conditions of preload dependency, which has actually been observed in healthy humans [45] and in patients with cardiac pacemakers, in whom diaphragmatic contractions were induced via the pacemaker [46]. Interestingly, D'Alonzo and Krachman have also shown that poor diaphragm biomechanics may lead to decreased cardiac output [47].…”
Section: Cardiac Functionmentioning
confidence: 99%
“…A recent study conducted by Aliverti et al [45,48] demonstrated that the modulation of the splanchnic vascular bed as a result of an increase in intraabdominal pressure via diaphragmatic contraction contribute to inferior vena cava blood return, that is, during inspiration, splanchnic venous return is favoured, whereas, during expiration, a venous return of femoral blood flow below the entry of the hepatic vein is preferred. The consequence is that abdominal breathing promotes an extra blood volume mobilisation (from splanchnic circulation) increasing net venous return to inferior vena cava, that is, diaphragmatic inspiration implies that inferior vena cava venous return is facilitated primarily by the central translocation of blood from the vessels of the abdomen and is not the result of facilitation of venous return from the lower limbs [49].…”
Section: Cardiac Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…All individuals were positioned in seated position on a backless bench and centralized in a system of six cameras previously calibrated according to the manufacturer's recommendations and previously published studies [24][25][26] . Subjects were requested to remain motionless breathing freely for 180 seconds.…”
Section: Assessment Of Chest Wall Volumes and Pepmentioning
confidence: 99%
“…Este método não possui diferenças significativas nos dados quando comparados com outros métodos de diagnóstico da mecânica toracoabdominal (Aliverti, 2008;Layton et al, 2013). É possível mensurar a cada ciclo respiratório, variáveis de volume e de tempo dos três compartimentos da parede torácica e dos dois hemitórax, além das variáveis de assincronia toracoabdominal (Romagnoli et al, 2008;Aliverti et al, 2010;Boudarham et al, 2013). Por todas essas razões o POE tem ganhado grande destaque nos últimos anos, nas pesquisas sobre a mecânica toracoabdominal, mas por ser uma tecnologia recente ainda carece de mais estudos.…”
Section: Com O Avanço Tecnológico Foi Desenvolvido O Pletismógrafounclassified